Alone Yet Not Alone: Frankia Lives Under the Same Roof With Other Bacteria in Actinorhizal Nodules - Ghodhbane-Gtari, Faten; D’Angelo, Timothy; Gueddou, Abdellatif; Ghazouani, Sabrine; Gtari, Maher; Tisa, Louis S. (Frontiers in Microbiology, 2021)
Actinorhizal plants host mutualistic symbionts of the nitrogen-fixing actinobacterial genus Frankia within nodule structures formed on their roots. Several plant-growth-promoting bacteria have also been isolated from actinorhizal root nodules, but little is known about them. We were interested investigating the in planta microbial community composition of actinorhizal root nodules using culture-independent techniques. To address this knowledge gap, 16s rRNA amplicon and shotgun metagenomic sequencing was performed on DNA from the nodules of Casuarina glauca. DNA was extracted from C. glauca nodules collected in three different sampling sites in Tunisia, along a gradient of aridity ranging from humid to arid. Sequencing libraries were prepared using Illumina Nextera technology and the Illumina HiSeq 2500 platform. Genome bins extracted from the metagenome were taxonomically and functionally profiled. Community structure based off preliminary 16s rRNA amplicon data was analyzed via the QIIME pipeline. Reconstructed genomes were comprised of members of Frankia, Micromonosopora, Bacillus, Paenibacillus, Phyllobacterium and Afipia. Frankia dominated the nodule community at the humid sampling site, while the absolute and relative prevalence of Frankia decreased at the semi-arid and arid sampling locations. Actinorhizal plants harbor similar non-Frankia plant-growth-promoting-bacteria as legumes and other plants. The data suggests that the prevalence of Frankia in the nodule community is influenced by environmental factors, with being less abundant under more arid environments.